INCLUSIVE PRODUCTION OF INTERMEDIATE MASS FRAGMENTS IN 20Ne+Ag,Au INTERACTIONS AT 20-60 MeV/nucleon - Papadakis, N. H.; et al., - (HNPS Advances in Nuclear Physics, 2020)
Energy spectra and angular distributions of intermediate mass fragments were measured at 20, 30, 40, 50 and 60 MeV/nucleon incident energies. Assuming two prevailing origins, fragmentation and evaporation (or fission), the measured energy spectra and angular distributions are reproduced by emission from two moving sources. The dependence of the parameters extracted for the sources on the fragment charge and on the incident energy is discussed. The distinctive role of fission in the case of the gold target is stressed. Xuclear fragmentation cross sections deduced from the moving source analysis are given and discussed for the two systems.